A Chlorhexidine- Agar Plate Culture Medium Protocol to Complement Standard Broth Culture of Mycobacterium tuberculosis - Asmar, Shady; Chatellier, Sonia; Mirande, Caroline; van Belkum, Alex; Canard, Isabelle; Raoult, Didier; Drancourt, Michel (Frontiers in Microbiology, 2016)
The culture of Mycobacterium tuberculosis using parallel inoculation of a solid culture medium and a liquid broth provides the gold standard for the diagnosis of tuberculosis. Here, we evaluated a chlorhexidine decontamination-MOD9 solid medium protocol versus the standard NALC-NaOH-Bactec 960 MGIT protocol for the diagnosis of pulmonary tuberculosis by culture. Three-hundred clinical specimens comprising 193 sputa, 30 bronchial aspirates, 10 broncho-alveolar lavages, 47 stools and 20 urines were prospectively submitted for the routine diagnosis of tuberculosis. The contamination rates were 5/300 (1.7%) using the MOD9 protocol and 17/300 (5.7%) with the Bactec protocol, respectively (P < 0.05, Fisher exact test). Of a total of 50 Mycobacterium isolates (48 M. tuberculosis and two Mycobacterium abscessus) were cultured. Out of these 50, 48 (96%) isolates were found using the MOD9 protocol versus 35 (70%) when using the Bactec protocol (P < 0.05, Fisher exact test). The time to positivity was 10.1 ± 3.9 days versus 14.7 ± 7.3 days, respectively (P < 0.05, Student's t test). These data confirmed the usefulness of parallel inoculation of a solid culture medium with broth for the recovery of M. tuberculosis in agreement with current recommendations. More specifically, chlorhexidine decontamination and inoculation of the MOD9 solid medium could be proposed to complement the standard Bactec 960 MGIT broth protocol.